Analisis Perawatan Mesin Kapal dengan Metode Reliability Centered Maintenance (RCM) di PT Jasa Armada Indonesia Tbk - Azhari, Hafiz; Ganap, Jimmy Greei; Nisah, Firda Ainun (Fakultas Teknik Universitas Tulang Bawang, 2024)
Maintenance of the ship is a task aimed at ensuring that the ship continues to operate in a normal and seaworthy condition. This work is related to the ship's machinery system and other equipment on board. If the ship does not receive regular maintenance, it can impact the condition and performance of the ship. By implementing Reliability Centered Maintenance (RCM), information about the steps needed to ensure optimal operation of the engine or equipment can be obtained. RCM is a method used to develop Preventive Maintenance. In Time Directed (TD), there are two components, namely the schottel Asd component and the valve on the cylinder head. In Condition Directed (CD), there are three components found in the three pipe components: fuel pipe, oil, and engine coolant. In Failure Finding (FF), there are four components found in the seachast component, injector pump, fuel filter, and air. Based on the application of the RCM method used, the recommended maintenance actions for the Finding Failure (FF) category include daily, weekly, and monthly inspection activities. Meanwhile, for the Time Directed (TD) category, maintenance actions involve scheduling component replacements based on predetermined intervals. Keywords: FMEA, LTA, Maintenance, RCM